Improved Seasonal Prediction of European Summer Temperatures With New Five‐Layer Soil‐Hydrology Scheme. Issue 1 (11th January 2018) - Bunzel, Felix; Müller, Wolfgang A.; Dobrynin, Mikhail; Fröhlich, Kristina; Hagemann, Stefan; Pohlmann, Holger; Stacke, Tobias; Baehr, Johanna
Abstract: We evaluate the impact of a new five‐layer soil‐hydrology scheme on seasonal hindcast skill of 2 m temperatures over Europe obtained with the Max Planck Institute Earth System Model (MPI‐ESM). Assimilation experiments from 1981 to 2010 and 10‐member seasonal hindcasts initialized on 1 May each year are performed with MPI‐ESM in two soil configurations, one using a bucket scheme and one a new five‐layer soil‐hydrology scheme. We find the seasonal hindcast skill for European summer temperatures to improve with the five‐layer scheme compared to the bucket scheme and investigate possible causes for these improvements. First, improved indirect soil moisture assimilation allows for enhanced soil moisture‐temperature feedbacks in the hindcasts. Additionally, this leads to improved prediction of anomalies in the 500 hPa geopotential height surface, reflecting more realistic atmospheric circulation patterns over Europe. Key Points: New five‐layer soil‐hydrology scheme improves seasonal prediction of European summer temperatures Improvements likely due to more realistic land‐atmosphere coupling and large‐scale circulation Hindcast skill significantly higher for more recent years compared to earlier years